Validitas Pop-Up Craft Berbasis Kearifan Lokal Untuk Mengenal Huruf dan Angka Siswa Tunagrahita - Icha Silvia; Alfina Noor Aini; Alia Amrina Rosyada; Teguh Samodra; Siti Masfuah (PGSD Universitas Muria Kudus, 2022)
This research aims to describe the validity of Pop-Up Craft media based on local wisdom to recognize letters and numbers for mentally retarded students at SDLB Negeri Cendono Kudus.This research was designed with a Research and Development (RD) research design with the research subjects being mildly mentally retarded students in grade 1 at SLB Negeri Cendono Kudus. This research is part of research and development which consists of preliminary study, development and validation stages. In the validation stage, it is carried out with the aim of knowing the suitability of the media being developed. Validation was carried out by 2 experts, namely media experts and material experts. The data collection technique in this research uses non-test techniques. The instrument used is the Pop-Up Craft media validation sheet in terms of media suitability and material suitability. The data analysis technique was carried out descriptively quantitatively.The results of media validation carried out by media experts showed that the average score of validation results from the aspect of media suitability was 4.09, which means it is suitable for implementation for students. Meanwhile, the results of media validation in terms of material feasibility aspect obtained an average score of 4.13, which means it is suitable for implementation. Results Based on data analysis, it can be concluded that the Pop-Up Craft media based on local wisdom for recognizing letters and numbers is valid and can be used in learning for mentally retarded students.